by Rory Cannon
Last Updated January 16, 2018 09:20 AM

isn't 1^i=1? because i^i = (i x 1)^i = i^i x 1^i = i ^i? or we could use e^PIi instead because Ill be disproving i to the i later e^PIi = -1 1^PI = 1 1^PIi = 1^i e^PIi x 1^i = e^PIi x 1^PIi e^PIi x 1^PIi = (e x 1)^PIi (e x 1)^PIi = e^PIi = -1 e^PIi x 1^i = e^PIi 1^i = 1

that is simple algebra

i^i = x i^4i = x^4 i^4i = (i^4)^i x^4 = 1^i x^4 = 1 x = 1, -1, i, or -i

simple algebra

e^PIi = -1 e^2PIi = 1 e^-2PI = 1^i e^-2PI = 1

somebody disprove this

simple algebra

- ServerfaultXchanger
- SuperuserXchanger
- UbuntuXchanger
- WebappsXchanger
- WebmastersXchanger
- ProgrammersXchanger
- DbaXchanger
- DrupalXchanger
- WordpressXchanger
- MagentoXchanger
- JoomlaXchanger
- AndroidXchanger
- AppleXchanger
- GameXchanger
- GamingXchanger
- BlenderXchanger
- UxXchanger
- CookingXchanger
- PhotoXchanger
- StatsXchanger
- MathXchanger
- DiyXchanger
- GisXchanger
- TexXchanger
- MetaXchanger
- ElectronicsXchanger
- StackoverflowXchanger
- BitcoinXchanger
- EthereumXcanger